Combination of MALDI-TOF Mass Spectrometry and Machine Learning for Rapid Antimicrobial Resistance Screening: The Case of Campylobacter spp. - Feucherolles, Maureen; Nennig, Morgane; Becker, Sören L.; Martiny, Delphine; Losch, Serge; Penny, Christian; Cauchie, Henry-Michel; Ragimbeau, Catherine (Frontiers in Microbiology, 2022)
While MALDI-TOF mass spectrometry (MS) is widely considered as the reference method for the rapid and inexpensive identification of microorganisms in routine laboratories, less attention has been addressed to its ability for detection of antimicrobial resistance (AMR). Recently, some studies have assessed its potential application together with machine learning for the detection of AMR in clinical pathogens. The scope of this study was to investigate MALDI-TOF MS protein mass spectra combined with a prediction approach as an AMR screening tool for relevant foodborne pathogens, such as Campylobacter coli and Campylobacter jejuni. A One-Health panel of 224 C. jejuni and 116 C. coli strains were phenotypically tested for seven antimicrobial resistances, i.e. ciprofloxacin, erythromycin, tetracycline, gentamycin, kanamycin, streptomycin and ampicillin, independently, and were submitted, after an on- and off-plate protein extraction, to MALDI Biotyper analysis, which yielded one average spectra per isolate and type of extraction. Overall, high performance was observed for classifiers detecting susceptible as well as ciprofloxacin and tetracycline resistant isolates. A maximum sensitivity and a precision of 92.3% and 81.2%, respectively, were reached. No significant prediction performance differences were observed between three on- and off-plate types of protein extractions. Finally, three putative AMR biomarkers for fluoroquinolones, tetracyclines and aminoglycosides were identified during the current study. Combination of MALDI-TOF MS and machine learning could be an efficient and inexpensive tool to swiftly screen certain AMR in foodborne pathogens, which may enable a rapid initiation of a precise, targeted antibiotic treatment.